Taking sides: A reflection on ‘partisan anthropology’ (Medicine Anthropology Theory, 2020)
This think piece argues for a ‘partisan anthropology’. Building on lessons learned through my research about the practices of postmastectomy breast reconstruction in France and Italy, I reflect on the role of the researcher in fieldwork. In my own research, I acted as neither a militant nor an activist in the field, that is, I did not actively participate in the initiatives I observed. However, in the analysis stage, I decided to side with the patients I had met: my aim was to understand their experience of the illness and the therapies available, as well as their sometimes difficult relationship with the medical system. Having decided to take the patients’ side, I conducted a ‘partisan anthropology’. These reflections are intended as an effort to fully recognize the legitimacy and the scientific character of a partisan anthropology, building on previous arguments for militant and activist anthropology.